Effect of iron addition on mAb productivity and oxidative stress in Chinese hamster ovary culture. (18th June 2021) - Graham, Ryan J.; Mohammad, Adil; Liang, George; Fu, Qiang; Kuang, Bingyu; Polanco, Ashli; Lee, Yong Suk; Marcus, R. Kenneth; Yoon, Seongkyu
Abstract: Trace metals play a critical role in the development of culture media used for the production of therapeutic proteins. Iron has been shown to enhance the productivity of monoclonal antibodies during Chinese hamster ovary (CHO) cell culture. However, the redox activity and pro‐oxidant behavior of iron may also contribute toward the production of reactive oxygen species (ROS). In this work, we aim to clarify the influence of trace iron by examining the relationship between iron supplementation to culture media, mAb productivity and glycosylation, and oxidative stress interplay within the cell. Specifically, we assessed the impacts of iron supplementation on (a) mAb production and glycosylation; (b) mitochondria‐generated free hydroxyl radicals (ROS); (c) the cells ability to store energy during oxidative phosphorylation; and (d) mitochondrial iron concentration. Upon the increase of iron at inoculation, CHO cells maintained a capacity to rebound from iron‐induced viability lapses during exponential growth phase and improved mAb productivity and increased mAb galactosylation. Fluorescent labeling of the mitochondrial hydroxyl radical showed enhanced environments of oxidative stress upon iron supplementation. Additional labeling of active mitochondria indicated that, despite the enhanced production of ROS in the mitochondria, mitochondrial membrane potential was minimally impacted. By replicating iron treatments during seed train passaging, the CHO cells were observed to adapt to the shock of iron supplementation prior to inoculation. Results from these experiments demonstrate that CHO cells have the capacity to adapt to enhanced environments of oxidative stress and improve mAb productivity and mAb galactosylation with minimal perturbations to cell culture.